Abuela - Dorros, Arthur; Kleven, Elisa (New York : Dutton Children's Books, 1991)
While riding on a bus with her grandmother, a little girl imagines that they are carried up into the sky and fly over the sights of New York City.
Decoding demand: 73 (high) Semantic demand: 74 (high) Syntactic demand: 70 (high) Structure demand: 83 (very high)
510L
Accelerated Reader
Accelerated Reader AR
Keywords: Imagination -- Juvenile fiction; Flight -- Juvenile fiction; Grandmothers -- Juvenile fiction; Hispanic Americans -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; #OwnVoices - Latinx